“Je ne sçai quoi”. On Animal Imagery, Evolution and Beauty - Bredekamp, Horst; Thurner, Kolja (Captures)

(untitled) (Figura, Centre de recherche sur le texte et l'imaginaire, 2022)
The essay tries to plea for incorporating concepts of evolutionary and animal imagery into an open theory of the image, that extends beyond the realm of human artifice and must no longer be viewed with an anthropocentric focus. Turning to images that are not human-made, we try to explore different image phenomena and connect them to non-human concepts of “Beauty” as historically developed by Charles Darwin’s underappreciated theory of “Sexual Selection” and, before him, trailblazed by William Hogarth.